Assessment of the level of leadership diseases in the presidency of sports clubs in Kurdistan region of Iraqi - Saleh, Adris; Aziz, Khaled (Humanities Journal of University of Zakho, 2022)
This research aims at: - Identify the level of leadership diseases among the heads of sports clubs in Kurdistan Region of Iraq and what are the most common diseases from the points of view of the members of the administrative bodies. Then the use of the descriptive approach in a survey and correlational style that is appropriate and the nature of the research, and the research community included members of the administrative bodies of sports clubs in Kurdistan region of Iraqi who are (612) members, representing (102) sports clubs, while the main research sample consisted of (428) members of an administrative body in sports clubs participating in the activities of Kurdistan football Association, and they represented (67) sports clubs distributed on grades ( excellent, first and second ) and the research tool included the preparation of a questionnaire for the leadership diseases of sports clubs presidents, and the researchers used the following statistical methods ( percentage, arithmetic mean, standard deviation, simple correlation coefficient, Cronbach’s alpha coefficient, Pearson correlation coefficient, coefficient of determination). Though these results, the researchers reached several conclusions, the most important of which are: 1-the levels of leadership diseases of sports clubs presidents varied between low and medium. 2-sports clubs suffer from some leadership diseases that negatively affect their performance Execution of tasks and duties optimally. The researchers recommended several recommendations, the most important of which are: 1-paying attention to the concept of leadership diseases in sports clubs through the adoption of wise leadership that encourages the establishment of a positive work atmosphere based on knowledge and scientific aspects in implementing its programs and policies. 2-An effective psychological encouragement to increase work and various activities.